The Amish secret wish [large type] - Hilton, Laura V., 1963- (Hidden Springs novel, 2021)
"Waitress Hallie Brunstetter has a secret: she writes a popular column for her Amish paper under the pen name GHB. When Hallie receives a letter from a reader asking to become her pen pal, she reluctantly agrees. She can't help but be drawn to the compassionate stranger, never expecting him to show up in Hidden Springs looking for GHB . . . or for him to be quite so handsome in real life. But after losing her beau in a tragic accident, Hallie won't risk her heart--or her secrets--again. If Kiah didn't already feel so connected to GHB, Hallie would be a perfect wife--and it seems most of Hidden Springs's would-be matchmakers agree! Though Hallie is peculiarly opposed to uncovering GHB's true identity, she understands Kiah almost as well as his mystery pen pal. The longer he searches for GHB, the more Kiah finds himself hoping Hallie will be holding the pen that first captured his heart. But will Hallie ever trust Kiah with the truth about her identity . . . and her feelings for him?"--